2021
DOI: 10.1002/adem.202100820
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hot‐Melt Extrusion Method to Produce Hydroxyapatite/Polycaprolactone Composite Filaments

Abstract: The aim of this work is to develop a single‐step process to produce hydroxyapatite/polycaprolactone (HAp/PCL) composite filaments for 3D printing of bone scaffolds by fused deposition modeling (FDM). The HAp/PCL composite filaments are produced by hot‐melt extrusion, with direct in situ blending. For practical purposes, the effect of PCL particle size on filament homogeneity and printability is assessed between PCL in powder and pellet form. The effect of HAp content on processing parameters and filament prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Surprisingly, the material extrusion method has rarely been used for scaffold fabrication, probably due to the lack of suitable materials and control methods [21]. Historically, solvent casting has been the main method, with only a few studies focusing on hot-melt extrusion, although using higher HA contents which, in return, influences printability parameters, involves the use of more expensive printers, and increases the presence of cell byproducts [26][27][28][29]33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, the material extrusion method has rarely been used for scaffold fabrication, probably due to the lack of suitable materials and control methods [21]. Historically, solvent casting has been the main method, with only a few studies focusing on hot-melt extrusion, although using higher HA contents which, in return, influences printability parameters, involves the use of more expensive printers, and increases the presence of cell byproducts [26][27][28][29]33].…”
Section: Discussionmentioning
confidence: 99%
“…Excluded scaffolds and parameters were tested and those which failed were either not extruded (temperature too low), too much extruded (temperature too high, low speed, or high flow factor), or the pores were interrupted (high speed or low temperature) (Supplementary Figure S2). Until now, the precise parameters for PCL/HA concentration had only partially been reported and limited to successful scaffold fabrication to expensive 3D printers [33]. We have precisely described the temperatures and speed required for each composition, reporting the causes of failure in the fabricated scaffolds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the 3D printed scaffolds can be alternative to solvent-processed scaffolds. Gerdes et al [ 24 ] and Zavřel et al [ 25 ] prepared 3D printed PCL/HAP scaffolds for bone tissue engineering. 3D scaffolds can easily be prepared at large scale since the process is free of solvents, and the scaffolds with different architectures can be prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been observed that particles can be isolated from the filament surface because of the presence of a plastic skin around them, thus preventing their bioactivity. [258] A possible solution to this problem is alkaline erosion of the final scaffold surface to better expose the bioactive agent; [259,260] still, this process adds a further step in the device production that increases the degree of complexity of the entire fabrication pipeline and also damages the structural stability if not correctly controlled. As also noted elsewhere, [42] when moving from traditional techniques to additive manufacturing, it is important to take into account the specific requirements of the printing process in the early stage of material development.…”
Section: In Vitromentioning
confidence: 99%